Germination responses of four native terrestrial orchids from south-west Western Australia to temperature and light treatments - Nikabadi, S.; Bunn, E.; Stevens, J.; Newman, B.; Turner, Shane; Dixon, Kingsley (Springer Netherlands, 2014)
We report an investigation into the impact of temperature and illumination on in vitro symbiotic and asymbiotic germination of the threatened taxon Caladenia huegelii, and three other orchid spp. namely—Caladenia latifolia, Microtis media and Pterostylis sanguinea, all species from south-west Western Australia, a recognized biodiversity hotspot. High symbiotic germination on oatmeal agar (OMA + fungal symbionts specific to each species) was recorded in three species in continuous dark incubation i.e. C. huegelii seeds (98 % germination at 25 °C), and M. media and P. sanguinea (93 and 98 % respectively at 20 °C). Highest symbiotic germination for C. latifolia (100 %) was observed at 15 and 20 °C under light treatment (12/12 h light/dark). Low temperature incubation (10 °C) significantly suppressed symbiotic germination/development of seedlings across all species. Asymbiotic media treatments assessed (OMA minus fungal symbionts, Pa5 and ½ MS), failed to stimulate any germination with C. latifolia seeds at 20 °C in either light or dark treatments after an 8 week incubation period. Seeds of M. media sown onto ½ MS medium resulted in higher germination in all developmental stages (3–5) in dark treatment than OMA and Pa5. Seeds of P. sanguinea sown onto ½ MS medium resulted in higher overall germination in all developmental stages (3–5) in light and dark incubation compared to OMA and Pa5. OMA supported the highest asymbiotic germination (100 %) in both light and dark incubation with M. media (only to stage 3) but did not support germination and development with other spp. tested.Caladenia huegelii seeds reached developmental Stage 3 (i.e. germinated), but only on Pa5 medium and only at a relatively low rate in either light (2.6 %) or dark (2.1 %). Germination was higher and development of seedlings faster overall in all test species in symbiotic compared with asymbiotic media treatments. P. sanguinea seeds demonstrated the best response (among species tested) to asymbiotic germination on ½ MS with 40–53 % of germinated seeds spread over developmental stages 3–5 in light or dark incubation (at 20 °C) respectively. Illumination had no effect on fungal symbiont growth across all species, however incubation temperature treatments (10, 15, 20 and 25 °C) affected fungal growth rate. Growth of the fungal symbionts of C. huegelii, M. media and C. latifolia demonstrated significantly lower activity at 10 °C, but the cumulative radial growth rate of the P. sanguinea fungal symbiont reached 64 cm2 after only 2 weeks at all temperatures tested, including 10 °C. The study highlights differences in symbiotic and aysmbiotic germination and early protocorm development in vitro between co-occurring herbaceous terrestrial Australian orchid taxa in response to variations in basal media, temperature and light.